ANALISIS RISIKO PORTOFOLIO DENGAN MENGGUNAKAN METODE SIMULASI MONTE CARLO (STUDI PADA PERUSAHAAN YANG TERDAFTAR INDEKS LQ45 DI BURSA EFEK INDONESIA PERIODE 2015-2018) - Indria Astuti; Burhanudin Burhanudin; Baiq Nurul Suryawati (Distribusi - Journal of Management and Business, 2020)
In this paper a discussion on portfolio risk analysis will be conductedmethod Monte Carlo Simulation usingusing calculation of Value at Risk (VaR) as the maximum estimate of losses in the portfolio. The use of Monte Carlo Simulation to analyze portfolio risk is done so that risk can be measured more accurately based on random value generator generated by repetition of 1000 iterations, which are designed to describe the risk of a particular asset. A portfolio is a combination of two or more individual shares. In calculating portfolio risk analysis, what needs to be done first is portfolio formation first. The formation of portfolios in this study uses themethod Single Index Model. The data used in this study are stock data for the LQ45 index for the period of 2015 to 2018. The selection of shares in the LQ45 category is because the liquidity of stocks classified as LQ45 is very liquid and many interested in the stock market. Based on the results of calculations, it shows that stocks that make up an optimal portfolio include in the first semester there are 4 stocks, namely: GGRM, BMTR, SILO, ASRI. In semester 2 there is 1 share that forms the optimal portfolio, namely ITMG shares. In semester 3 there are 4 shares, namely: JSMR, GGRM, SCMA, and TBIG. In semester 4 there are 7 shares, namely: INTP, MPPA, WIKA, PGAS, PWON, PTPP and AALI. In semester 5 there are 9 stocks, namely: ELSA, LPKR, PPRO, AALI, PTPP, ASRI, ADRO, AKRA and ANTM. In semester 6 there are 2 shares, namely SSMS and AALI. In the 7th semester there were 7 stocks, namely: SRIL, BSDE, TLKM, BRPT, SSMS, TPIA, and LPPF. In the 8th semester there were 6 stocks, namely: SMRA, ANTM, PTPP, TLKM, SMGR, and SRIL. Then the LQ45 stock portfolio VaR value is obtained at 0.04534961, which means that the loss to be suffered by investors will not exceed Rp. 45,349,610 if the initial investment is Rp. 1,000,000,000.